The Effect Of Giving Traditional Herbs Uyup Uyup Jamu For Smooth Breast Milk Flow To Mothers In Post-Part In Pangarungan Village, Torgamba District, Regency South Labuhanbatu Year 2025 - Pebrinawanti Br Saragih; Ruseni ㅤ; Tisnilawati ㅤ; ㅤ Masni; Rhina Chairani Lubis; Lili Nurmalia (JOURNAL EDUCATIONAL OF NURSING(JEN), 2026)
Jamu uyup uyup or in other words (gepyokan) is a herbal medicine used to increase breast milk production in breastfeeding mothers. This study aims to determine the effect of giving traditional herbal concoctions of jamu uyup uyup on the smooth flow of breast milk to postpartum mothers. This study is quantitative using primary data obtained directly from questionnaires, the population of this study is postpartum mothers in Pangarungan II Village with a total of 25 people. The sampling technique uses a purposive sampling method. Data analysis uses univariate analysis, and bivariate analysis. From the results of the bivariate analysis study, it was shown that there was a significant influence between the frequency of breastfeeding per day, the volume of breast milk, and breast feelings with the provision of traditional herbal concoctions of uyup-uyup using the chi-square test, the value was 0.00, which means it was significant because the p-value <0.05. The conclusion of this study was that there was an influence of the provision of traditional herbal concoctions of uyup-uyup on the smoothness of breast milk to postpartum mothers in Panggarungan II Village in 2025. The results of the analysis showed a significant relationship between the influence of giving uyup-uyup herbal concoctions with the frequency of breastfeeding per day (p-value = 0.00), breast milk volume (p-value = 0.02), and breast feelings before and after breastfeeding (p-value = 0.00).